Experimental justification of the use of synthetic products for strengthening soils of buildings and structures - Sagybekova, Akmaral; Kabdullagazy, Nauruzbayev; Orazbayeva, Dinara; Alimtaikyzy, Pana (Innovaciencia, 2022)
Introduction: The purpose of the research of the scientific article is to study the stability of slopes and their reinforced with synthetic materials and the influence of reinforcement elements on the stress and deformation of joint soil massifs. Materials and Methods: At article are given: the tests were carried out in the task of the head of the tray with the use of synthetic materials. Results and Discussion: The use of technical materials for solving the issues of strengthening slopes and slopes is very relevant today. Synthetic geosynthetics of various production methods are required to perform the following functions in combination: reinforcement - reinforcement with materials of slopes, walls of pits and slopes of embankments, bases as a result of the redistribution of stresses arising in soil materials, and the soil mass under the action of loads from vehicles and its own weight; protection - prevention, exclusion or slowdown of the process of soil erosion, prevention of interpenetration of products of contacting layers; filtration - prevention, exclusion (slowdown), solution of the process of penetration of pound particles into drainages (filter) or their removal (reverse filter); drainage - acceleration, slowing down the arrival, removal of water filtration; waterproofing - reduction or diversion, exclusion of water inflow into the soils of the working layer of the subgrade. Conclusions: In tests, synthetic meshes are used to ensure the strength of the edge of the slope at loads of 100 kPa, 200 kPa, 300 kPa: a method for applying the method of strengthening the edge of the slope, with the most compacted base soil and the use of reinforcement elements, is proposed, which leads to an increase in the strength of subsiding soil bases and the edge of the slope during the construction of buildings and structures.
Keywords: Geosynthetic Material; Reinforcement Of Slopes And Slopes; Soil Reinforcement